The Social, Economic, and International Relations Impact of the 2023 Israel-Hamas War - Mbah, Ruth Endam; Hultquist, Laura; Fonkem, Beryl Ngum; Mbah, Emmanuel Fonjindam (Advances in Social Sciences Research Journal, 2024)
Hamas’s attack on Israel on October 7th, 2023, is not the first of its type. The Israeli-Palestine tension can be traced back to 1947 following the UN Partition Plan that divided the British Mandate of Palestine into Jewish and Arab Nations. Following Britain’s withdrawal from the Peninsula, the Jewish leaders declared the State of Israel, sparking the first Arab-Israeli conflict and this tension has worsened over the years. We use Thomas Hobbes’s Social Contract to explain the tension between both parties. According to Hobbes, man lives in a State of Nature which is characterized by war and the continuous fear of death. This fear of death is the reason why man enters into a contract (Social Contract). There have been diverse schools of thought as to the origin of the Israeli-Palestine tension. Some believe it is the 1947 UN Partition Plan, others believe it is the June 1967 war, while others believe it is religion. Regardless of the original cause, it is evident that both parties have retained severe casualties over the years. Hence, the purpose of this paper is to review the economic, social, and international relations consequences of the 2023 Israel-Hamas war. The current war has had several social consequences: refugee migrations, lack of basic survival necessities, withdrawal of medical aid groups, starving refugees, desolated cities, and allegations of rape and sexual torture. Economically, the war has led to the loss of income from economic activities, an increase in oil prices, reignited inflation, high-interest rates, increased government expenditures, and exchange rates. It has also impacted international relations among nations due to a split in support between Israel and Palestine. Nevertheless, there is an allowance for further study because this paper is limited only to the social, economic, and international relations impact of the war.